The consumer-industrial complex. (Economist, 2011)
The article discusses how businesses are implementing consumer technology like smartphones, tablet computers, and online social networking. Topics discussed include the startup business Voalté, which modifies smartphones for use by doctors and nurses; customized business social networking sites protected by company firewalls like salesforce.com, Socialtext, and Yammer; and customized mobile device applications, or apps, designed to promote companies' products or streamline company processes.